High tech garbage can help engineering colleges to improve hands-on education - Lucena, Samuel Euzédice de [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents a discussion on the potential use of high tech garbage, including electronic waste (e-waste), as a source of mechanisms, sensors and actuators, that can be adapted to improve the reality of microprocessor systems labs, at low cost. By means of some examples, it is shown that entire subsystems withdrawn of high tech equipments can be easily integrated into existing laboratory infrastructure. As examples, first a precision positioning mechanism is presented, which was taken from a discarded commercial ink jet printer and interfaced with a microprocessor board used in the laboratory classes. Secondly, a read/write head and its positioning mechanism has been withdrawn of a retired CD/DVD drive and again interfaced with the microprocessor board. Students who have been using these new experiments strongly approve their inclusion in the lab schedules. © 2011 IEEE.
Keywords: Hands-on education; Electrical engineering labs; High tech garbage; Electronic waste; Optical encoders